IMPROVING STUDENTS’ VOCABULARY COMPETENCE BY CONSTRUCTING GRAMMATICAL AND LEXICAL COLLOCATION AT GR STUDENTS’ VOCABULARY COMPETENCE BY CONSTRUCTING GRAMMATICAL AND LEXICAL COLLOCATION AT GRADE XI IN WELLINGTON INTELLIGENCE SCHOOL - Laura. A Simanjuntak; Sondang Manik; Erika Sinambela; Edi Suprayetno (Jurnal Mutiara Pendidikan Indonesia, 2022)
This study aims to: (1) find out whether collocation improves students' vocabulary competence (2) find the type of collocation that is most developed in students' vocabulary competence. This research combined qualitative data and quantitative data, where quantitative data was used to support qualitative data. The subject in this research were high school students of grade XI Wellington Intelligence School. The number of students was 39 students consisting of two classes (22 students in science class and 17 students in social class). The instruments used consist of interviews, observations, documents, and tests. This study adopted descriptive statistics to describe the main features of the data set. The average score of each test, including pre-test and post-test, were used to analyze the data. The results showed that collocation can improve students' vocabulary competence. The students' initial average was 70 for science students and 68.23 for social students. While the final average value showed an increase in the value of 82.72 for science students and 80.58 for social studies students. There were more student errors in the interpretation of lexical collocations than in the interpretation of grammatical collocations. Keywords: Vocabulary Competence, Building Grammar, Lexical Collocation